Improvement of Earthquake Source Mechanism Using Waveform Inversion in the Indo-Australian Oceanic Plate - Nurma Aisyah; Muksin; Nazli; Sandriadi, Wahyu (UIR PRESS, 2026)
The Indo-Australian Oceanic Plate region is an active and complex subduction zone. Tectonic activity in this area generates various types of faults, including thrust, strike-slip, and normal faults, reflecting the dynamic deformation of the lithosphere. This study aims to refine earthquake source parameters using waveform inversion based on the Bayesian Bootstrap approach. Seven earthquake events with magnitudes greater than 5, occurring between 2010 and 2025, were analyzed to obtain more accurate parameters, including location, depth, origin time, duration, magnitude, and fault plane orientation (strike, dip, and slip). Waveform data were retrieved from the USGS catalog and processed using the Grond and Pyrocko software. The inversion results indicate significant shifts in initial parameters, with misfit values below 0.5, demonstrating a high level of agreement between synthetic and observed waveforms. The tectonic interpretation of the inversion outcomes reveals a relationship between hypocenter depth, fault type, and subduction zone geometry. This research is expected to contribute to a better understanding of earthquake source mechanisms and serve as a scientific reference for disaster mitigation efforts in the Indo-Australian Plate region.